Evidence for a modifying pathway in SMA discordant families: reduced SMN level decreases the amount of its interacting partners and Htra2-beta1 - Helmken, Claudia; Hofmann, Yvonne; Schoenen, Frank; Oprea, Gabriela; Raschke, Heidrun; Rudnik-Sch neborn, Sabine; Zerres, Klaus; Wirth, Brunhilde (Human genetics, 2003)
Proximal spinal muscular atrophy (SMA) is a neuromuscular disorder caused by homozygous mutations of the SMN1 gene. SMN1 interacts with multiple proteins with functions in snRNP biogenesis, pre-mRNA splicing and presumably neural transport. SMN2, a nearly identical copy of SMN1, produces predominantly exon 7-skipped transcripts, whereas SMN1 mainly produces full-length transcripts. The SR-like splicing factor Htra2-beta1 facilitates correct splicing of SMN2 exon 7 through direct interaction with an exonic splicing enhancer within exon 7. In rare cases, siblings with identical 5q13-homologues and homozygous absence of SMN1 show variable phenotypes, suggesting that SMA is modified by other factors. By analysing nine SMA discordant families, we demonstrate that in all families unaffected siblings produce significantly higher amounts of SMN, Gemin2, Gemin3, ZPR1 and hnRNP-Q protein in lymphoblastoid cell lines, but not in primary fibroblasts, compared with their affected siblings. Protein p53, an additional SMN-interacting protein, is not subject to an SMN-dependent regulation. Surprisingly, Htra2-beta1 is also regulated by this tissue-specific mechanism. A similar regulation was found in all type I-III SMA patients, although at a different protein level than in discordant families. Thus, our data show that reduced SMN protein levels cause a reduction in the amount of its interacting proteins and of Htra2-beta1 in both discordant and non-discordant SMA families. We provide evidence that an intrinsic SMA modifying factor acts directly on the expression of SMN, thus influencing the SMA phenotype. Further insights into the molecular pathway and the identification of SMA modifying gene(s) may help to find additional targets for a therapy approach.